Reflection on Negotiations Between Indonesia and Tesla, Inc. Regarding Electric Vehicle Investment in 2020-2024 - Jason Fernando (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Indonesia is one of the countries in Southeast Asia rich in nickel reserves, so this has become an attraction for foreign investors to compete to invest amid a drastic increase in market demand for lithium batteries for electric vehicles. Tesla, Inc. became one of the investors who showed interest in the potential for establishing a lithium-ion battery factory for electric vehicles. Indonesia is aware of Tesla's enthusiasm in trying to conduct intense negotiations and lobbying because these MNCs have several advantages in terms of advanced features and acceleration, as well as adhering to green principles. The author's aim in raising this issue is to reflect on Indonesia's long process of building government-to-business negotiations and lobbying with Tesla, where Indonesia sees this opportunity as a step to pursue national interests. The method used in this research is based on a literature study through secondary data collection. The findings from this research are that both Indonesia and Tesla use a rational approach and integrative strategy in negotiating investment cooperation. However, Indonesia's optimistic attitude is reflected in experiencing various challenges, including competition from competitors from other countries and unsustainable nickel mining problems.